EFEKTIFITAS MENGUNYAH APEL JENIS ANNA DIKUPAS DAN TANPA DIKUPAS TERHADAP PENURUNAN INDEKS PLAK - Nawang Novida Pratiwi; Silvia Prasetyowati (Jurnal Kesehatan Gigi (Dental Health Journal), 2020)
Chewing apple is often called the natural way to brush teeth, because apple has large particles that must be chewed again before swallowing, and also apple is fruits that contain fiber so that it encourages the secretion of saliva, the type of local apple which has the highest fibers content namely anna’s apple, where the most of fibers which was found in the fruit is also found on it’s skin. Problem: the high of plaque index score of grade IV-A students in Tambakwedi 508 Surabaya year 2019. The purpose of the study: to was known the effectivity of chewing anna’s apple which is peeled and non peeled to decrease plaque index. Research Methods: Which was used is pra experimental research, with a pre-posttest design group. Data collection methods by observation. Results of the study: Plaque index before and after chewing anna’s apple which is peeled of grade IV-A students in Tambakwedi 508 there was a decrease from the medium category to the good category, plaque index before and after chewing anna’s apple which is non peeled of grade IV-A students in Tambakwedi 508 there was a decrease from the medium category to the good category, there was difference the effectivity of chewing anna’s apple which is peeled and non peeled to decrease plaque index.